Perancangan Tata Letak Fasilitas Perakitan Box Radio Panel dengan Menggunakan Metode Blocplan pada PT Mobilkom Telekomindo - Umarella, Rafif Fadhlurrahman; Diah Damayanti, Dida; Budiasih, Endang (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
In the manufacturing industry, designing efficient facility layouts is critical to increasing productivity, reducing costs, and improving quality. PT Mobilkom Telekomindo, which operates in the trunking and SCADA radio communications sector, is working on a radio panel box procurement project from PT Pelindo. This research aims to evaluate the existing layout which still has workstations that are far apart and design a new layout to reduce assembly time using the BLOCPLAN algorithm. The results show that the new layout reduces the material transfer distance from 293.5 meters to 169 meters (42.4% reduction), as well as reducing the material transfer time from 10 minutes 27 seconds to 6 minutes 3 seconds (58.02% reduction).